CYTOPROTECTIVE AND ANTIOXIDANT EFFECTS OF THE METHANOL EXTRACT OF EREMOMASTAX SPECIOSA IN RATS. - Amang, Perfusion A.; Tan, Paul V.; Patamaken, Simon A.; Mefe, Martial N. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Ethno-botanical information shows that Eremomastax speciosa is used in the traditional management of various stomach complaints including gastro-duodenal ulcers. Materials & Methods: In this study, we tested the cytoprotective potential of the whole plant methanol extract (100-200 mg/kg, p.o), against HCl/ethanol, absolute ethanol, cold/restraint stress rats, and pylorus legated rats pre-treated with indomethacin. The effects of the extract on gastric lesion inhibition, the volume of gastric juice, gastric pH, gastric acid output, mucus production and gastric peptic activity were recorded. Oxidative stress parameters were measured in blood and gastric tissue samples obtained from the animals in all the models tested. Results: The extract significantly (p<0.05), reduced the formation of cold/restraint ulcers by (31-60%, inhibition), completely inhibited (100%), and the formation of lesions induced by HCl/ethanol at the highest dose, but was less effective against absolute ethanol (22-46% inhibition). The extract (200 mg/kg), significantly reduced lesion formation (P<0.01), gastric acidity (P<0.01), and volume of gastric secretions (P<0.05), in the indomethacin/pylorus ligation model, and did not affect the activity of pepsin in gastric juice. Blood concentrations of antioxidant enzymes (catalase, SOD and GSH), increased significantly and MDA concentrations decreased in all models tested. Conclusion: Cytoprotection by E. speciosa methanol extract was attributed to its ability to reduce acid secretion, and to enhance mucosal defence and in vivo antioxidant status.